Pronoun Variations and Code-Switching as Intimacy and Politeness Strategy; A Corpus Study of Community Interaction in Balikpapan - Muhammad Adam; Siti Hafsah (Hasanuddin University, 2023)
Socio-pragmatic competency is related to the ability of people to use language in accordance with certain social contexts or certain social conditions. The various use of honorific forms and the variation of “self” and “other” reference forms become a very important instrument in maintaining politeness as an aspect of socio-pragmatic. Those variations show the socio-pragmatic aspect of the participants involved. This paper aims to examine the use of various pronouns among the member of one neighborhood community in Balikpapan, East Kalimantan. The methodology of this study is descriptive, corpus-based study by collecting data from WhatsApp group conversations and conducting analysis using AntConc tools. The focus of the paper is to examine the pronoun variations of “self” and “other” references including the choice of pronoun code-switching. Although in Balikpapan, colloquial Indonesian is used in daily conversation, for politeness and intimacy, the code-switching of pronouns is observed. Thus, other than Indonesian common pronouns, the other pronoun used is the Javanese pronoun first person singular (kulo) “I/me/my” and Banjarese “ulun”. Furthermore, the honorific address of Pak Haji (given to a person who has conducted a Hajj pilgrimage from Mecca) is found and is used as second-person and third-person singular pronouns. Then, there is also “Pak RT” (The chief of the community association) that is addressed using the term to refer to him, both as a second-person and third-person pronoun. These extensive variations and code-switching of pronouns observed in a small neighborhood show that pronoun variations and pronouns code-switching is an important tool in everyday conversation to maintain intimacy and politeness to achieve a harmonious living in a heterogeneous society.